PENERAPAN DATA MINING UNTUK MENENTUKAN STRATEGI PROMOSI PRODUK INDUSTRI KREATIF UMKM KOTA DENPASAR PASCA PANDEMI COVID 19 - I Made Artana; Nengah Widya Utami (Jurnal Informatika Teknologi dan Sains, 2022)
In era of the Covid-19 pandemic MSMEs in Denpasar City has increased but not significantly compared to previous years. Entering the industrial revolution 4.0 and society 5.0 requires business actors to be more creative and innovative. In this case, it is very important for MSMEs to determine the right strategy, especially in terms of product promotion so that they can compete in expanding the market and increasing income, so that it is expected to revive the economy of Denpasar City. The Denpasar City Government has a large number of MSME data, but this data has not been used properly. One of the data mining methods is K-Means clustering. The stages of data mining in this research process include: 1)data pre-processing which includes data cleaning, data integration, data selection and data transformation; 2)the application of data mining methods using the K-Means clustering algorithm, which at this stage has the same characteristics and characteristics in certain clusters, and finally 3)data interpretation and evaluation of the information and knowledge patterns generated from the mining process. The cluster results obtained from this study are expected to be a reference in policy making to determine the promotion strategy of creative industry products in Denpasar City.